The Study on Bali Tourism Village Management towards Four Dimensions of Experience Economy - Hardini, Widi; Agustini Karta, Ni Luh Putu; Putu Suarthana, Jimmy Harry (E-Journal of Tourism; Volume 2 Number 1 (March 2015), 2015)
Tourism as one of the largest industries in the world economy is now entering a new era, the experience economy. The concept adopted by Pine and Gilmore in 1998, where there was a shift in the company’s economic orientation. This concept emphasizes the customer value and suitable in services industry, especially in Tourism industry. In the new economic era, customer satisfaction is no longer the main things, but delivering comprehensive services to create a memorable experience. Bali tourism industry focuses on cultural development and preservations. There is a linkage between the experience economy concept and tourism village concept, which is at the participation level of all components in the development (management, tourists and the society). Therefore, the concept of experience economy is suitable to be applied in the development of tourism villages. This research conducted to elaborate and analyze the classification of tourism village product and the levels of tourist participation towards four dimensions of experience economy concept. Through qualitative research methods will generate a depth understanding of managing tourism village by creating tourist memorable experience.
Keywords: experience economy, management, memorable experience, tourism village